Annual performance assessment of an off‐grid and self‐sufficient sustainable climate refuge for hot arid climates - Fariha Niaz (14778319) (2023)
To overcome the problem of walking in the scorching heat and to encourage people to use more public transport (ie, trams and metros), the idea of sustainable climate refuge shelter is highly needed. In this study, the proposed shelter includes semi-transparent photovoltaic cells located on the roof integrated with batteries to keep the system running at nighttime and in unfavorable irradiation conditions. An atmospheric water generator for freshwater production is employed for drinking and water misting in addition to a vapor compression cooling system with a fan. Freshwater is collected by extracting water from humid air through cooling with dehumidification. The system is analyzed thermodynamically through energy and exergy efficiencies. The overall energy and exergy efficiencies of the system are 19.45% and 9.58%, respectively. The electrical efficiency of the photovoltaic cells decreases from 16.87% to 15.24% with an increase in cell temperature from 309 K to 315 K. Hourly analysis of the proposed system for the whole year is performed to evaluate the energy profile. The proposed system generates electricity in winters that is sufficient to keep the system operational for 2 days (only for drinking water requirement), but in the summers, only 24 h due to extensive cooling load. The effects of several parameters such as irradiance, ambient temperature, relative humidity, transmittance, and occupancy rate are studied. Other Information Published in: Energy Science & Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ese3.1025